Troubling Diversity and Inclusion: Racialized Women’s Experiences in the Canadian Armed Forces - George, Tammy (Atlantis, 2020)
This article centers on the lived experiences of racialized servicewomen in the Canadian Armed Forces (CAF). Drawing on qualitative interviews with racialized servicewomen, I problematize the function of contemporary diversity and inclusion initiatives within the CAF. Focusing on the intersection of race and gender in their lives provides a way to think through structural inequities within the Canadian military. By examining how these structures of power operate within the CAF, we are better situated to understand how current diversity and inclusion initiatives work to consolidate hegemonic power. Informed by feminist critical race theories and critical geography, I trace the experiences of racialized servicewomen to understand how they make sense of their inclusion and belonging and how they assess their everyday experiences in the context of diversity and inclusion strategies presented by the CAF. Their lived experiences reveal the importance of race and gender in their lives, and expose the limits of diversity and inclusion practices, particularly, in their inability to address deeper structural issues of white supremacy, heteronormativity, and patriarchy within the CAF. While concepts of diversity and inclusion are typically concerned with the inclusion of those on the margins, this research suggests that we must seriously interrogate the theoretical, practical, and political work of diversity and inclusion initiatives within a multicultural context. Troubling inclusion and diversity in the CAF demands we disrupt structures of dominance and reflect on how to re/conceptualize and re/integrate meaningful difference more substantially throughout institutional life in multicultural Canada.